2016
DOI: 10.1089/thy.2015.0665
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Carcinoma: Association Between Germline DNA Variant Markers and Clinical Parameters

Abstract: Background: Papillary thyroid cancer (PTC) is reported to be highly heritable in epidemiological studies. Genome-wide association studies (GWAS) have uncovered several variants associated with PTC predisposition. It remains unknown whether these variants might contribute to better clinical stratification of PTC patients. Methods: In order to assess the usefulness of germline genetic analyses in the management of PTC patients, the genotypes of five variants (rs965513, rs944289, rs116909374, rs2439302, and rs966… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 44 publications
1
35
1
Order By: Relevance
“…Our clinical results also showed that the variants of NRG1 are associated with lymph node metastasis in thyroid cancer, especially in BRAF V600E -mutated PTC. A recent report supported this association, showing an association between a variant of NRG1 (rs2439302) and lymph node metastasis in PTC26. Although we did not demonstrate the direct effects of the increased expression of NRG1 on tumour aggressiveness, we could postulate a possibility that the increased expression of NRG1 in the thyroid tissue, which is associated with identified variants, might influence the development or progression of thyroid cancer.…”
Section: Discussioncontrasting
confidence: 63%
“…Our clinical results also showed that the variants of NRG1 are associated with lymph node metastasis in thyroid cancer, especially in BRAF V600E -mutated PTC. A recent report supported this association, showing an association between a variant of NRG1 (rs2439302) and lymph node metastasis in PTC26. Although we did not demonstrate the direct effects of the increased expression of NRG1 on tumour aggressiveness, we could postulate a possibility that the increased expression of NRG1 in the thyroid tissue, which is associated with identified variants, might influence the development or progression of thyroid cancer.…”
Section: Discussioncontrasting
confidence: 63%
“…It was found that larger tumor size and extrathyroidal expansion were associated with risk allele of the variant rs965513. Association with LNM and tumor multifocality was found with the rs2439302 suggesting an important function in clinical course, a role beyond predisposition to PTC (Jendrzejewski et al 2016).…”
Section: Ptcsc3 (Papillary Thyroid Carcinoma Susceptibility Candidate 3)mentioning
confidence: 93%
“…Moreover, downregulated NONHSAT037832 has been significantly associated with LNM and tumor size (larger tumor) suggesting that NONHSAT037832 and rs2439302 of PTCSC3 could serve as a potential prognostic marker of PTC, as it clearly showed a high value to differentiate between PTCs and noncancerous tissues . The rs2439302 of PTCSC3 has also been associated with LNM and tumor multifocality reflecting a pivotal role in clinical course (Jendrzejewski et al 2016). Besides, LOC100507661 has been frequently detected as a highly expressed lncRNA in PTC and ATC cases, and significantly associated with LNM and the classical BRAF mutation .…”
Section: Lncrnas: Prognostic Markers In Thyroid Cancermentioning
confidence: 99%
“…Familial non-medullary thyroid carcinoma (FNMTC) represents roughly 5% of thyroid malignancies, and no reproducible susceptibility genes have been consistently associated with the diagnosis (93)(94)(95). Given the role of NXX2-1 role in thyrocyte differentiation, proliferation, and survival (96), germline mutations in NKX2-1 have been postulated to play a role in predisposition to thyroid malignancies (97)(98)(99). A single case series demonstrated a recurrent loss-of-function variant of NKX2-1 (p.A339V) in four of 20 independent kindreds affected by both papillary thyroid carcinoma (PTC) and multinodular goiter (MNG; ref.…”
Section: Nkx2-1 Syndromementioning
confidence: 99%